A Small Discussion on the Guiding Significance of the Theory of Diet Recurrence and Heat That Has Not Yet Dissipated in the Recovery Period of Pediatric Febrile Illnesses in the Plain Questions Treatise on Heat - Liang, Pengbo; Zhang, Jinhu (Journal of Contemporary Medical Practice, 2024)
Pediatric febrile illnesses are relatively common in clinical practice, especially respiratory and digestive system diseases are most common, which can be said to be common and frequent. Whether in the acute or recovery period, improper dietary feeding and protective measures occur from time to time, which can easily lead to recurrence, delay, aggravation and other diseases, and how to prevent pediatric problems in this area needs to be solved. Based on the theory of diet recurrence and heat that has not yet dissipated, it is important to discuss the role and influence of diet and feeding on the recovery period of children's diseases, so as to guide the parents to have a reasonable diet during the process of the disease, to promote the recovery of children's diseases as soon as possible, and to avoid the disease recurrence, prolongation, aggravation, and not yet dissipated.